Auditory stimuli enhance MDMA-conditioned reward and MDMA-induced nucleus accumbens dopamine, serotonin and locomotor responses - Feduccia, Allison A. (Brain Res Bull, 2008)
MDMA (3,4-methylenedioxymethamphetamine), also known as ecstasy, is a popular drug often taken in environments rich in audio and visual stimulation, such as clubs and dance parties. The present experiments were conducted to test the notion that auditory stimulation influences the rewarding effects of MDMA. In Experiment 1, a conditioned place preference (CPP) procedure was conducted in which rats received MDMA (1.5 mg/kg, s.c.) in a distinctive environment accompanied by music (65–75 dB), white noise (70 dB), or no added sound. Animals were pretreated with saline on alternating days in an alternate environment. Results revealed CPP in animals exposed to white noise during MDMA trials. For Experiment 2, rats from Experiment 1 had access to operant levers that delivered intravenous MDMA (0.5 mg/kg/inj) or saline (0.1 ml) on alternate days in the presence or absence of the same types of auditory stimuli as previously experienced. After three each of MDMA and non-reinforced (saline) sessions, animals were tested for NAcc DA and 5-HT responses to MDMA (1.5 mg/kg) or saline under the same stimulus conditions. Findings revealed that NAcc DA and 5-HT increased after an MDMA injection, and both DA and 5-HT were significantly highest in animals exposed to music during the test session. These results indicate that paired sensorial stimuli can engage the same systems activated during drug use and enhance neurochemical and behavioral responses to MDMA administration.